2003
DOI: 10.1124/mol.63.5.1094
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transport of Nucleoside Analog Drugs by the Human Multidrug Resistance Proteins MRP4 and MRP5

Abstract: The human multidrug resistance proteins MRP4 and MRP5 are organic anion transporters that have the unusual ability to transport cyclic nucleotides and some nucleoside monophosphate analogs. Base and nucleoside analogs used in the chemotherapy of cancer and viral infections are potential substrates. To assess the possible contribution of MRP4 and MRP5 to resistance against these drugs, we have investigated the transport mediated by MRP4 and MRP5. In cytotoxicity assays, MRP4 conferred resistance to the antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
266
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(283 citation statements)
references
References 27 publications
16
266
1
Order By: Relevance
“…The electrophoretic mobility of vitro for drug resistance [32], but no evidence of resistance to Pt drugs in cells overexpressing exogenous MRP1 has been provided [33]. In the present study, the employed gain of function approach suggests that, at least in ovarian carcinoma models, oxaliplatin and cisplatin are substrates for MRP1 and MRP4, which appear to transport also topotecan, a known MRP4 substrate, and 6-mercaptopurine, one of the most important substrates of MRP4 [34][35][36].…”
Section: Discussionmentioning
confidence: 68%
“…The electrophoretic mobility of vitro for drug resistance [32], but no evidence of resistance to Pt drugs in cells overexpressing exogenous MRP1 has been provided [33]. In the present study, the employed gain of function approach suggests that, at least in ovarian carcinoma models, oxaliplatin and cisplatin are substrates for MRP1 and MRP4, which appear to transport also topotecan, a known MRP4 substrate, and 6-mercaptopurine, one of the most important substrates of MRP4 [34][35][36].…”
Section: Discussionmentioning
confidence: 68%
“…MRP/ABCC family members can be subdivided into two groups: (a) ABCC1-3, ABCC6, and ABCC10, which contain 17 transmembrane segments; and (b) ABCC4, ABCC5, ABCC11, and ABCC12, which lack one of the transmembrane regions and have only 12 transmembrane segments (5). Some studies have shown that later group members (although ABCC12 is still under investigation) are transporters of cyclic nucleosides and nucleoside analogues due to the active efflux of the monophosphorylated metabolites of these drugs (6,7,10). Furthermore, recent transfection studies have showed that ABCC5 and ABCC11 are able to efflux FdUMP, which is the monophosphorylated and active metabolite of 5-FU (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Parental HEK293 cells (293 human embryonic kidney cells) and the MRP4-overexpressing HEK293/ 4.63 cells were gifts of P Borst (The Netherlands Cancer Institute, Amsterdam, The Netherlands) (Wielinga et al, 2002). HEK293/4.63 cells were reported to express significantly more MRP4 (Reid et al, 2003) without overexpression of other ABC drug transporters and were cultured as previously described (Wu et al, 2005). The ovarian IGROV-1 cells were obtained from the Developmental Therapeutics Program, NCI.…”
Section: Cell Culturementioning
confidence: 99%